Providing Safe and Effective Preventative Antiretroviral Prophylaxis to HIV-exposed Newborns via a Novel Drug Delivery System in Tanzania. Issue 9 (September 2016) - Dahinten, Alexander P.; Dow, Dorothy E.; Cunningham, Coleen K.; Msuya, Levina J.; Mmbaga, Blandina T.; Malkin, Robert A.
Abstract : Background: In developing countries, antiretroviral therapy provides life-saving treatment to HIV-positive women and their children before, during and after birth. However, supply chain challenges such as long distances, medication shortages and nonfacility deliveries often compromise consistent access to prophylactic treatment for at-risk infants. A proposed intervention to address these challenges, often referred to as the "Pratt Pouch, " allows for liquid-formulation medications, such as nevirapine (NVP), to be repackaged into single-dose pouches. These pouches are distributed antenatally. Methods: HIV-positive women at Kilimanjaro Christian Medical Centre in Moshi, Tanzania received 14 pouches each containing a single dose of NVP for prevention of mother-to-child transmission. Women were trained on how to open the pouch and dispense the medication to their infants after delivery. All participating women were asked to return to Kilimanjaro Christian Medical Centre 7–14 days after delivery, where infant blood spots were collected to assess NVP levels. Results: All enrolled women (21/21) administered NVP to their infants within 24 hours of birth. All enrolled infants (22/22) had NVP blood concentrations over 100 ng/mL and exhibited no health concerns attributable to over or under dosing. Conclusions: The Pratt Pouch intervention provides a clinically appropriate solution for addressing liquid-formulation antiretroviral access challenges in developing countries.